1992
DOI: 10.1002/qre.4680080319
|View full text |Cite
|
Sign up to set email alerts
|

ESD induced degradation mechanisms of InGaAsP/InP lasers

Abstract: The sensitivity of InGaAsP/InP buried crescent lasers to ESD phenomena was deeply analysed, starting from the need to explain and prevent sudden failures during equipment manufacturing and test. Failure analysis allowed us to localize the degradation, which can be explained by means of a simple phenomenological model; finally a physical model was implemented trying to correlate the results of the failure analysis with the proposed failure mechanism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 2 publications
0
13
0
Order By: Relevance
“…High reliability is required from such LDs, and the authors have studied a significant reliability index, namely, the tolerance to electrostatic discharge (ESD). ESD-induced degradation has been investigated by other research institutions, and it has been shown that LD facets are destroyed by a forward-biased ESD test [1][2][3]. In addition, our analysis has demonstrated that the damage is related to melting caused by light absorption at an active layer of the facet, just as in the case of COD (Catastrophic Optical Damage) [4].…”
Section: Introductionmentioning
confidence: 82%
“…High reliability is required from such LDs, and the authors have studied a significant reliability index, namely, the tolerance to electrostatic discharge (ESD). ESD-induced degradation has been investigated by other research institutions, and it has been shown that LD facets are destroyed by a forward-biased ESD test [1][2][3]. In addition, our analysis has demonstrated that the damage is related to melting caused by light absorption at an active layer of the facet, just as in the case of COD (Catastrophic Optical Damage) [4].…”
Section: Introductionmentioning
confidence: 82%
“…Variations occurring at a weak injection level are directly associated with a leakage current due to shunt leakage paths. Depending on the structure, this last contribution is modelled by a resistance (R sh ) placed in parallel with the junction branch, as reported by Magistrali et al 17 . In our case, leakage current is lower than 10 −12 A, corresponding to the current resolution of the measurement system, Agilent-4156C (Deshayes et al 22 ).…”
Section: Electrical Characterizationsmentioning
confidence: 98%
“…Our assumption is based on the fact that defects are located at the P − -InGaAs/N + -GaAs interface with an initial concentration of defects N def x→0 . After 600 and 1200 h, defect concentration has increased in the active zone as shown in Figure 10 according to Equation (17). With Equation (18) it is possible to estimate the increase in the defect density in the middle of the active zone.…”
Section: Variations In P(t T) and Its Variation P(t T ) Before Anmentioning
confidence: 98%
See 2 more Smart Citations